Community Reading Park Development Training (TBM) - Solfema, Solfema; Bartin, Tasril; Pamungkas, Alim Harun (Universitas Negeri Padang, 2019)
ABSTRACTHealth is one of the conditions for a realized generation that is ready with a variety of future Information continues to grow as the development of education and technology. Information has become an important need of the community. A society that is rich in information will advance and develop in accordance with the development of science itself, otherwise the people who are left behind in their information will also be scattered from development and progress. One forum that can facilitate to keep abreast of information is Community Reading Gardens (TBM). For this reason, activities are carried out in the form of: 1) providing the competence and theoretical and applicative understanding in organizing Community Reading Gardens (TBM), 2) Establishing and developing Community Reading Gardens by providing facilities and infrastructure in accordance with program capabilities. Results 1) Increased competence and understanding of the community in the management of Community Reading Gardens (TBM), 2) Establishment of Community Reading Gardens (TBM) as a forum for collecting information for the community.Keywords: Training, Development, Community Reading Park (TBM)